Effectiveness of Contextual Teaching and Learning on The Ability to Mathematical Relational Understanding in Junior High School - Fita Nurhana; Ahmad Anis Abdullah (EduMa: Mathematics education learning and teaching, 2021)
The low ability of students' mathematical relational understanding is caused by the lack of student activity in learning and the lack of students' understanding of concepts and implementing concepts in real life. This study aims to determine the contextual teaching and learning model's effectiveness on students' relational understanding abilities on the prism and pyramid concept. This type of research uses a quasi-experimental research design with a non-equivalent control group design and sampling using the purposive sampling technique. The instrument used to determine the ability of relational understanding in the form of a description test is 9 questions that have been tested for feasibility. Based on statistical calculations, the experimental class average is 70.103 and the control class average is 63.25. After calculating the average difference test against the data, it is obtained tcount =1.793 and ttable=1.66. It can be concluded that the average mathematical relational understanding ability of students taught using the CTL learning model is better than that of conventional learning. Thus, it can be concluded that the Contextual Teaching and Learning (CTL) learning model is effective on students' mathematical relational understanding abilities